1995
DOI: 10.3354/cr005031
|View full text |Cite
|
Sign up to set email alerts
|

The role of individual terrain units in the water balance of wetland tundra

Abstract: The water balance of a High Subarctic wetland was measured in a newly established research basin near Churchill, Manitoba, Canada. Measurements spanned the growing season from early June through to the end of August 1991. The watershed was instrumented such that the water budget could be monitored over each of the dominant terrain unlts. The study basin has 5 major terrain types consisting of sedge-dominated wetland, upland lichen-heath, tundra lakes and ponds, willowbirch wetland, and open spruce forest, in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…2, summer 1991 was atypical of the 'normal' conditions that have been observed in the area over the last 50 yr with respect to both temperature and precipitation (Boudreau & Rouse 1995). Average temperatures for the months of June, July, and August 1991 were more than 3°C above normal.…”
Section: Studymentioning
confidence: 86%
See 2 more Smart Citations
“…2, summer 1991 was atypical of the 'normal' conditions that have been observed in the area over the last 50 yr with respect to both temperature and precipitation (Boudreau & Rouse 1995). Average temperatures for the months of June, July, and August 1991 were more than 3°C above normal.…”
Section: Studymentioning
confidence: 86%
“…8). Field studies suggest that, because of local advective effects, these small water bodies may play a larger role in the regional water balance than their areal coverage suggests (Bello & Smith 1990, Boudreau & Rouse 1995. For these reasons TM imagery should be compared with AVHRR to investigate the potential for improving the temporal coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBL are the largest contiguous wetland complex in North America, with thousands of lakes and ponds in the landscape (Keller et al, 2014;Dyke and Sladen, 2010) from impeded drainage due very low topographic gradients (Boudreau and Rouse, 1995) and the presence of permafrost. Ponds have been demonstrated to be stably stratified in the eastern HBL , while the very shallow (< 1 m) ponds in the western HBL are assumed to be well mixed by wind action (Bello and Smith, 1990).…”
Section: Study Site and Sampling Designmentioning
confidence: 99%
“…Ponds have been demonstrated to be stably stratified in the eastern HBL , while the very shallow (< 1 m) ponds in the western HBL are assumed to be well mixed by wind action (Bello and Smith, 1990). Ponds in the western HBL have been shown to be nutrient-limited (Eichel et al, 2014;Symons et al, 2012), restricted in surface and groundwater connection (Boudreau and Rouse, 1995), with steep banks and thick, organic sediments with dense mats of benthic blue-green, green, and diatomaceous algae (Macrae et al, 2004;Gray, 1987), with the dominant diatom genus being Denticula (Macrae et al, 2004). Symons et al (2012) showed the most abundant phytoplankton communities to be Chlamydomonas spp., Sphaerocystis spp., Diatoma spp., and Crugienella spp.…”
Section: Study Site and Sampling Designmentioning
confidence: 99%